Santa's twin - Koontz, Dean R. (Dean Ray), 1945-; Parks, Phil (New York : HarperPrism, 1996)
Two sisters save Christmas from Santa's evil twin brother who delivers worms, spiders, spinach, and Brussels sprouts candy.
1-2
Keywords: Christmas -- Fiction; Santa Claus -- Fiction; Stories in rhyme